EFEK BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. PEGADAIAN UNIT PLAMPANG - Roos Nana Sucihati; Lia Hidayati (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of the marketing mix and service quality on customer satisfaction at PT. Pegadaian Unit Plampang. The type of this study was associative study. The type of data used is quantitative obtained from primary data sources. The number of respondents in this study were 81 people who were obtained using the Slovin formula. The primary data used in this study were obtained through distributing questionnaires. All data that has been collected will then be processed using the SPSS program to be studied using techniques which include multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results of the study showed that the the marketing mix and service quality had a positive and significant effect on customer satisfaction at PT. Pegadaian Unit Plampang, either partially or simultaneously. The degree of influence of the marketing mix and service quality on customer satisfaction PT. Pampang Unit Plampang is 42.5%, while the remaining 57.5% is influenced by other variables not examined in this study, such as convenience, efficiency, trust in use, as well as customer perceptions of the usefulness of the service features provided.